Understanding online impulsive buying behavior: In the fashion industry - Pinto, Catarina Alexandra Santos (2021)
The study of impulsive buying has attracted the attention of researchers for over 70 years. However, there are few studies on the influential elements of impulsive online buying. Thus, this study seeks to fill this gap and explore the influence of the COVID-19 pandemic on impulsive online buying, which marketing stimuli trigger impulsive online buying, and, finally, the impact of product characteristics on consumers' impulsive behavior. A qualitative approach was used to reach the study objective, conducted through 16 individual interviews and four focus groups. The results obtained revealed that the COVID-19 pandemic, marketing stimuli, and product characteristics are determinant elements in prompt online impulsive purchases. That is, they all have a significant impact and make the consumer buy impulsively. This study contributes to the existing literature on impulsive online buying, resulting in essential knowledge for marketing regarding developing more appropriate and effective stimuli that can influence online impulsive buying behavior.